Fine-tuning stress responses by auxiliary feedback loops that sense damage repair - Mogk, Axel; Brave, Fabian den (The journal of cell biology, 2024)
Mogk and den Brave discuss exciting results from a comprehensive screen of heat shock response components in yeast, published in this issue by Pincus and colleagues (https://doi.org/10.1083/jcb.202401082). Their work reveals modulatory regulatory loops that fine-tune the timing of the shutdown of this highly conserved pathway.
Gesehen am 15.05.2025